2012
DOI: 10.1155/2012/473941
|View full text |Cite
|
Sign up to set email alerts
|

Prader-Willi Syndrome: Clinical Aspects

Abstract: Prader-Willi Syndrome (PWS) is a complex multisystem genetic disorder that shows great variability, with changing clinical features during a patient's life. The syndrome is due to the loss of expression of several genes encoded on the proximal long arm of chromosome 15 (15q11.2–q13). The complex phenotype is most probably caused by a hypothalamic dysfunction that is responsible for hormonal dysfunctions and for absence of the sense of satiety. For this reason a Prader-Willi (PW) child develops hyperphagia duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
74
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(79 citation statements)
references
References 92 publications
(95 reference statements)
2
74
0
3
Order By: Relevance
“…PWS is an imprinting genetic disorder caused by loss of expression of paternal chromosome 15q 3. First described in 1956 by Prader et al , PWS is a complex multisystem disorder in which clinical manifestations reflect hypothalamic and autonomic nervous system dysfunction 3–5.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PWS is an imprinting genetic disorder caused by loss of expression of paternal chromosome 15q 3. First described in 1956 by Prader et al , PWS is a complex multisystem disorder in which clinical manifestations reflect hypothalamic and autonomic nervous system dysfunction 3–5.…”
Section: Discussionmentioning
confidence: 99%
“…First described in 1956 by Prader et al , PWS is a complex multisystem disorder in which clinical manifestations reflect hypothalamic and autonomic nervous system dysfunction 3–5. Prevalence has been estimated between 1/15 000 and 1/25 000 live-births 3. While no structural hypothalamic defect has been found in PWS, DiMario and Burleson 5 have demonstrated that the primary disturbance in autonomic regulation exists primarily in parasympathetic function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The overeating behaviour seen in patients with PWS was once thought to be related to a "lack of will power". However it is now considered to be related to an abnormal satiety response and increased motivation for food (Elena et al, 2012;Yearwood et al, 2011). To date there are two relevant reviews identifying studies and offering opinion to the possible underlying mechanisms involved in patients with PWS and hyperphagia .…”
Section: Introductionmentioning
confidence: 99%
“…39 Based on initial results, serum levels of luteinizing hormone, FSH, and gonadal steroids (estradiol or testosterone) should be obtained after gonadotropin-releasing hormone stimulation. For induction of puberty in boys, monthly intramuscular injection of testosterone is used, with a gradual increase to adult doses at the end of puberty.…”
mentioning
confidence: 99%